Lionfish envenomation in Caribbean and Atlantic waters: Climate change and invasive species - Benjamin B. Norton, MD, MPH&TM; Scott A. Norton, MD, MPH, MSc (Wolters Kluwer, 2021)
The concept of emerging diseases is well understood; however, the concept of emerging injuries is not. We describe the introduction of two species of lionfish, native to the Indian and Pacific Oceans, into the warm shallow coastal waters of the Western Atlantic Ocean and the Caribbean Sea. Lionfish thrive in the same coastal waters that attract recreational swimmers, snorkelers, and divers. Because lionfish have ornate colors, people often swim close to have a better look. Lionfish have venomous spines and, in a defensive reaction, frequently envenomate curious humans. The fish are voracious predators and disrupt the coral ecosystems of the Atlantic. Furthermore, their range is spreading through a combination of lack of natural predators and the expansion of hospitable warm waters into higher latitudes as part of climate change.